Odpowiedzi

2010-03-21T13:49:55+01:00
7x+7 = 35
7x = 35-7
7x = 28 |:7
x = 4

2-x = 5-2
-x = 3-2
-x = 1 |:(-1)
x = -1

69-x = x+96
-x-x = 96-69
-2x = 27 |:(-2)
x = -13,5

½x+5 = x+8
0,5x-x = 8-5
-0,5x = 3 |:(-0,5)
x = -6
2010-03-21T13:51:00+01:00
7x+7=35
7x=35-7
7x=28
x= 4

2-x=5-2
-x=5-2-2
-x=1/:(-1)
x=-1

69-x=x+96
-x-x=96-69
-2x=27/:(-2)
x= -13.5

½x+5=x+8
½x-x=8-5
-½x=3/:(-½)
x= -6
1 4 1
2010-03-21T13:54:13+01:00
A) 7x + 7 = 35
7x = 35 - 7
7x = 28
x = 4
b) 2 - x = 5 - 2
-x = 5 - 2 -2
-x = 1
x = -1
c) 69 - x = x +96
-x - x = 96 - 69
-2x = 27
x = -13,5
d) ½x +5 = x +8
½x - x = 8 - 5
-½x = 3
x = -6